Modular DC‐DC converter with reduced current ripple and low voltage stress suitable for high voltage applications. (1st July 2022) - Babalou, Milad; Dezhbord, Morteza; Maalandish, Mohammad; Hosseini, Seyed Hossein; Islam, Md. Rabiul; Torkaman, Hossein
Abstract: In this paper, a couple inductor‐based dc‐dc boost converter with extensible capability is presented. In the proposed converter, attaching extensions to input section alleviates input current ripple. Furthermore, the current sharing performance between different phases operates beneficially by expanding optimized boost converters, especially when a partial inequality exists among different switches' duty cycles and leakage inductances. The voltage conversion ratio of the proposed converter is also additionally optimized by a series of VMR's output capacitors. Meanwhile, not only the voltage stress upon the main switches is decreased but also the all switches are managed to be turned on with zero current switching technique. The voltage spikes across MOSFETs are eliminated by using the recycling energy of leakage inductances on the clamp capacitor. The topology of the proposed converter, steady‐state analysis, and design procedure is presented to indicate the merits of the suggested converter. A prototype circuit with a three‐phase interleaved boost converter, two number of diode‐capacitor in each VMR, and output power 660 W and 40–800 V conversion ratio is experimented to corroborate the validity of the presented structure. Abstract : In this paper, a couple inductor‐based dc‐dc boost converter with extensible capability is presented. This paper proposes a better current sharing performance, reduced voltage stresses upon semiconductors along with increased voltage gains, and, finally, elimination of reverse recovery current problem in all diodes are mentioned as merits of the proposed topology.